The Chinese of Cuba and Peru: a historiographical review - Zapata, Antonio (2020)
This paper reviews the academic production regarding the Chinese inmigration to Cuba and Peru. It’s main inquiry is why both cases have produced so different results despite a similar background and social origin. The answer is politics: the Chinese in Cuba fought in the Independence campaign and were quickly assimilated as part of the army that defeated Spanish colonialism. Years later, the Cuban revolution expropiated small business of the Chinese, and they were forzed to massively migrate to the U.S.A. On the other hand, the Chinese in Peru rebelled against the plantation regime during the War of the Pacific, in which Chile defeated a joint Peru-Bolivia Alliance. A portion of the culíes helped the Chilean army, and subsecuently the community suffered a lot to be accepted as part of the forces that constituted the peruvian nation. Nevertheless, the Peruvian Chinese progressively assimilated successfully, through their contribution to the service economy, including their gastronomic innovation, which captivated the Peruvians. In this way, paradoxically, the Cuban Chinese, which integrated faster and successfully, ended up leaving Cuba, while the Peruvian Chinese, which suffered to be accepted, have ended becoming one of the most accepted and in constant renovation even as of today. Likewise, this paper reviews the contemporary history of the relations between China and both countries, observing how China’s new position as the second World Power has defined the social and economical life of the Latin-American Chinese.